2014
DOI: 10.1371/journal.pone.0107428
|View full text |Cite
|
Sign up to set email alerts
|

MID1 Catalyzes the Ubiquitination of Protein Phosphatase 2A and Mutations within Its Bbox1 Domain Disrupt Polyubiquitination of Alpha4 but Not of PP2Ac

Abstract: MID1 is a microtubule-associated protein that belongs to the TRIM family. MID1 functions as an ubiquitin E3 ligase, and recently was shown to catalyze the polyubiquitination of, alpha4, a protein regulator of protein phosphatase 2A (PP2A). It has been hypothesized that MID1 regulates PP2A, requiring the intermediary interaction with alpha4. Here we report that MID1 catalyzes the in vitro ubiquitination of the catalytic subunit of PP2A (PP2Ac) in the absence of alpha4. In the presence of alpha4, the level of PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 54 publications
3
64
0
Order By: Relevance
“…As shown previously, the B-box1 domain is required for the binding and poly-ubiquitination of alpha4 but not PP2A [1,11]. As shown previously, the B-box1 domain is required for the binding and poly-ubiquitination of alpha4 but not PP2A [1,11].…”
Section: The P151l B-box1 Mutant Maintains Its E3 Ligase Activitysupporting
confidence: 77%
See 2 more Smart Citations
“…As shown previously, the B-box1 domain is required for the binding and poly-ubiquitination of alpha4 but not PP2A [1,11]. As shown previously, the B-box1 domain is required for the binding and poly-ubiquitination of alpha4 but not PP2A [1,11].…”
Section: The P151l B-box1 Mutant Maintains Its E3 Ligase Activitysupporting
confidence: 77%
“…The B-box1 domain is critical for poly-ubiquitination of alpha4 and PP2Ac [1,11]. The structure of the B-box1 domain is similar to RING E3 ligase domains [22][23][24][25][26], consisting of two b-strands and one a-helix and held together by the coordination of two zinc ions (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MID1 consists of the RING finger (RING), zinc-binding B-box-1 (B1) and B-box-2 (B2) domains, followed by a coiled-coil region (CC) and C-terminal subgroup one signature (COS), fibronectin type III repeat (FN3) and PRY-SPRY domains [Quaderi et al, 1997;Du et al, 2014]. Functionally impaired MID1 variants have a lower affinity for microtubules, causing degradation of protein phosphatase 2A (PP2A), a microtubule-associated protein.…”
mentioning
confidence: 99%
“…Patients suffer from multiple malformations of the ventral midline as a consequence of mutations in the MID1 gene (25,26). In previous studies, Mid1 has been described to regulate protein phosphatase 2A (PP2A) stability (27)(28)(29)(30). PP2A/α4 is not the only known substrate, because recently it was shown that Mid1 interacts with the GLI regulator Fu, leading to a cytoplasmic retention of GLI3 in cancer cells (31).…”
mentioning
confidence: 99%